Analysis Of The Sensory Quality Of Jelly Candy With The Addition Of Tamarillo Fruit Pure - Lailasari, Noviana; Holinesti, Rahmi; Yuliana, Yuliana; Mustika, Sari (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This research was motivated by the relatively short shelf life of tamarillo fruit and the absence of research on the effect of adding tamarillo fruit puree to jelly candy. In this research, tamarillo fruit was used to make natural coloring in jelly candy. This study aims to analyze the effect of using tamarillo fruit puree (0%, 25%, 50%) on the quality of jelly candy including shape, color, aroma, texture and taste. This type of research is a pure experiment using a completely randomized design (CRD) method with three treatments and three repetitions. The data collection technique was carried out by carrying out organoleptic tests involving fifteen semi-trained panelists who were students of Culinary Arts majoring in Family Welfare Science, Faculty of Tourism, Hospitality, Padang State University. The results obtained from the organoleptic test will be continued with statistical analysis using the F test with organoleptic tests on the quality of jelly candy in terms of (shape, color, aroma, texture and taste. In this study there were differences in the color quality of the first layer and the second layer on jelly candy. Color quality of the first layer with results (Fhit = 277.71 > Ftab 3.20) which is from an average of 1.00, 3.02 to 3.20 (Fhit = 5.54 > Ftab 3.20) where the average is 3.51, 3.29 to 2.93. Taste quality with results (Fhit = 117.14 > Ftab 3.20) where the average is 1, 00, 3.13 to 3.13.